Genesis of theoretical grounds for the use of triangulation in sociological research - Kuchko, Elena E.; Urban, Dariya O. (Journal of the Belarusian State University. Sociology, 2021)
The article considers the history of formation of qualitative and quantitative methodological approaches in sociology. The  historical reconstruction of the fundamental ideas of representatives of these areas makes it possible to better understand their relationship, to determine the possibilities of their interaction in the study of social reality. In this regard, the article analyses the qualitative and quantitative strategy of sociological research taking into account their ontological, epistemological, axiological and methodological principles. A meaningful analysis of the three «waves», the stages of sociological cognition makes it possible to understand the specifics of the development of sociological knowledge, determine central ideas and values, and better understand the dynamics of the interaction of existing approaches and paradigms. Qualitative and quantitative methodological approaches in social sciences arose almost simultaneously, but their further development was extremely uneven, and their use to study and explain social reality for a long time was not based on the principles of parity interaction. The expansion of the practice of sociological research in a situation of high dynamics of social processes made it possible to increase the level of research culture, the understanding of values and cognitive differences in qualitative and quantitative methodologies made it possible and necessary to use them together. The basis for combining qualitative and quantitative methodological approaches is their functional additionality, which is expressed in the ability to most fully represent various aspects of the study of the same subject area. We are talking about methodological, conceptual triangulation as a strategy for the interaction of qualitative and quantitative approaches in the study of social problems using qualitative and quantitative methods for collecting and analysing sociological information. Such a technique increases the completeness and reliability of the received information, expands research capabilities.
Keywords: qualitative methodology; quantitative methodology; triangulation; research strategies in sociology